Assessment of antiangiogenic effect of imatinib mesylate on vestibular schwannoma tumors using in vivo corneal angiogenesis assay Laboratory investigation - (:unkn) unknown (AMER ASSOC NEUROLOGICAL SURGEONS, 2012)
Object. Angiogenesis and the platelet-derived growth factor (PDGF) pathway are active in the pathogenesis of vestibular schwannomas (VSs). The purpose of this study was to test whether imatinib mesylate (Gleevec), a PDGF receptor (PDGFR) blocker, reduces angiogenic capacity in sporadic VS and in VS associated with neurofibromatosis Type 2 (NF2) using a conical angiogenesis assay. Methods. From 121 VS tissue samples stored in the tumor bank at the Marmara University Institute of Neurological Sciences, 10 samples (6 from sporadic cases, 4 from NF2-associated cases) were selected at random for use in this study. Expression of PDGF-A and PDGF-B and their receptors was evaluated in sporadic and NF2-associated VS as well as in glioblastoma (GBM) and normal brain tissue by means of immunohistochemistry and Western blot analysis. Corneal angiogenesis assay was then used to evaluate the angiogenic capacity of tissue specimens from sporadic and NF2-associated VS with and without imatinib treatment as well as positive and negative controls (GBM and normal brain tissue). Results. The angiogenic potential of the sporadic and NF2-associated VS tumor tissue differed significantly from that of the positive and negative control tissues (p < 0.05). Furthermore, NF2-associated VS showed significantly lower angiogenic potential than sporadic VS (p < 0.05). Imatinib treatment significantly reduced the angiogenic potential in both the sporadic VS and the NF2-associated VS groups. The level of PDGF-A and PDGFR-alpha as well as PDGF-B and PDGFR-beta expression in sporadic VS and NF2-associated VS also differed significantly (p < 0.05) from the levels in controls. Additionally the level of PDGFR-beta was significantly higher in sporadic VS than in NF2-associated VS (p < 0.05). Conclusions. The findings of this study indicate that NF2-associated VS has significantly more angiogenic potential than sporadic VS and normal brain tissue. Additionally, imatinib reduces the angiogenic activity of both sporadic and NF2-associated VS. The authors conclude that imatinib may be a potential treatment for VS, especially for NF2-associated lesions that cannot be cured with resection or radiosurgery. (http://thejns.org/doi/abs/10.3171/2012.6.JNS112263)
Keywords: angiogenesis; corneal angiogenesis assay; oncology; vestibular schwannoma; neurofibromatosis Type 2; ENDOTHELIAL GROWTH-FACTOR; ACOUSTIC NEUROMAS; TYROSINE KINASE; FACTOR RECEPTOR; STEREOTACTIC RADIOSURGERY; NEUROFIBROMATOSIS TYPE-2; TARGETING ANGIOGENESIS; TAMING GLIOBLASTOMA; CLINICAL-ASPECTS; PDGF RECEPTORS